Assessing cassava breeding clones in two agroecologies in the Democratic Republic of Congo - Sikirou, M.; Mwangu, K.M.; Kayondo, S.I.; Agre, A.P.; Tata-Hangy, W.; Bakelana, T.; Adetoro, N.A. (2022)
Breeding is the most economical approach for controlling production constraints in cassava (Manihot esculenta Crantz) smallholder farms. This study aims at assessing the performances of elite cassava clones in the province of Kwilu, Democratic Republic of Congo (DRC). Three sets of trials were established using an alpha lattice and a randomized complete block designs in two contrasting locations, upland savanna and valley forest agroecologies. Eleven traits were used in phenotyping the cassava clones along with two checks varieties (local cultivar Biele and improved variety OBAMA). High heritability was recorded for the traits and it ranged from 0.52 to 0.75 except for yield (0.45). They are significant differences between the tested clones and the improved variety OBAMA. Overall, the Best Linear Unbiased Estimates (BLUEs) used for weighing in the selection index led to two candidate clones, KYK2016-048 and KYK2015-04 that outperformed both checks, Obama and Biele in this study and they could be potential candidates for variety replacement.